Interleukin-20 Acts as a Promotor of Osteoclastogenesis and Orthodontic Tooth Movement - Yuanbo Liu; Yilong Ai; Xuan Sun; Bowen Meng; Xi Chen; Dongle Wu; Lei Gan; Benyi Yang; Chaoran Fu; Yilin Wu; Yang Cao (Stem Cells International)
Objectives. Bones constitute organs that are engaged in constant self-remodelling. Osteoblast and osteoclast homeostasis during remodelling contribute to overall skeletal status. Orthodontics is a clinical discipline that involves the investigation and implementation of moving teeth through the bone. The application of mechanical force to the teeth causes an imbalance between osteogenesis and osteogenesis in alveolar bone, leading to tooth movement. Osteoimmunology comprises the crosstalk between the immune and skeletal systems that regulate osteoclast–osteoblast homeostasis. Interleukin- (IL-) 20, an IL-10 family member, is regarded as a proinflammatory factor for autoimmune diseases and has been implicated in bone loss disease. However, the mechanism by which IL-20 regulates osteoclast differentiation and osteoclastogenesis activation remains unclear. This study investigated the effects of IL-20 on osteoclast differentiation in a rat model; it explored the underlying molecular mechanism in vitro and the specific effects on orthodontic tooth movement in vivo. Methods. For in vitro analyses, primary rat bone marrow-derived macrophages (BMMs) were prepared from Sprague–Dawley rats for osteoclast induction. After BMMs had been treated with combinations of recombinant IL-20 protein, siRNA, and plasmids, the expression levels of osteoclast-specific factors and signalling pathway proteins were detected through real-time polymerase chain reaction, western blotting, and immunofluorescence staining. For in vivo analyses, IL-20 was injected into the rat intraperitoneal cavity after the establishment of a rat orthodontic tooth movement (OTM) model. OTM distance was detected by Micro-CT and HE staining; the expression levels of protein were detected through immunofluorescence staining. Results. In vitro analyses showed that a low concentration of IL-20 promoted preosteoclast proliferation and osteoclastogenesis. However, a high concentration of IL-20 inhibited BMM proliferation and osteoclastogenesis. IL-20 knockdown decreased the expression of osteoclast specific-markers, while IL-20 overexpression increased the expression of osteoclast specific-markers. Furthermore, IL-20 regulated osteoclast differentiation through the OPG/RANKL/RANK pathway. Overexpression of IL-20 could significantly upregulate RANKL-mediated osteoclast differentiation and osteoclast specific-marker expression; moreover, RANKL/NF-κB/NFATc1 acted as downstream signalling molecule for IL-20. In vivo analysis showed that OTM speed was significantly increased after intraperitoneal injection of IL-20; additionally, mechanical stress sensing proteins were markedly activated. Conclusions. IL-20 augments osteoclastogenesis and osteoclast-mediated bone erosion through the RANKL/NF-κB/NFATc1 signalling pathway. IL-20 inhibition can effectively reduce osteoclast differentiation and diminish bone resorption. Furthermore, IL-20 can accelerate orthodontic tooth movement and activate mechanical stress sensing proteins.